ANALISIS PERHITUNGAN DAN PEMOTONGAN PPh PASAL 21 KARYAWAN TETAP PADA PT. TELAGA BAKTI PERSADA TERNATE - Masrinah, Linath; Tinangon, Jantje J.; Gerungai, Natalia Y. T. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Taxes are an important component for the government in carrying out state activities in Indonesia, since the financing of routine expenditures as well as government development is largely derived from the tax sector. as it is known that tax revenue plays a vital role since the revenue from the oil and gas sector has decreased. The government in this case the Directorate General of Tax (DJP) always wanted to perform the task in terms of collecting tax revenue so that the nation's survival is maintained. Therefore, the Directorate General of Tax (DJP) is trying to get the tax collection in Indonesia on target by always trying to improve the service by updating the rules of tax collection that meet the requirements of justice, juridical, economic, financial and simple. This study aims to analyze the calculation and withholding of Article 21 Income Tax on the salary of PT. Telaga Bakti Persada Ternate whether it is in compliance with the provisions of the Taxation Law. No. 36 of 2008 Income Tax Income. This research uses Descriptive Research Method. The results of the research can be concluded that the calculation and withholding of income tax article 21 Income Tax on permanent employees of PT. Telaga Bakti Persada Ternate has done calculations and deductions in accordance with the provisions of the current law.Keywords: calculation and deduction of income tax PPh article 21, income tax, receipt income tax PPh article 21, accounting, income tax article 21, Tax Regulation.